Challenges to Provision of Adequate Medical Nutrition Therapy in a Critically Ill COVID-19 Patient Fed in the Prone Position. Issue 3 (July 2022) - Brown, Terry; Touger-Decker, Riva; Roberts, Susan; Reed, Diane; Matarese, Laura
Abstract : Adults with acute respiratory distress syndrome (ARDS) may experience enteral nutrition (EN) intolerance. They often require mechanical ventilation and other specialized management including prone positioning. There is a controversy as to whether patients fed in prone position experience more EN intolerance than when they are in supine position. This narrative review synthesizes the literature published between 2001 and 2021 in adults with ARDS who are fed EN while in the prone position to determine safety and tolerance. A case of an adult patient with Down syndrome who developed ARDS due to COVID-19 and required EN while in prone position is presented.